Phosphine-free Suzuki-Miyaura cross-coupling in aqueous media enables access to 2-C-aryl-glycosides. - Cobo, I; Matheu, M; Castillón, S; Boutureira, O; Davis, B (2012)
A general strategy for the synthesis of 2-aryl-glycals and their elaboration to 2-C-aryl-α-glycosides and 1,5-anhydro-2-C-aryl-2-deoxy alditols are described. The use of reliable, efficient phosphine-free Suzuki-Miyaura cross-coupling of 2-iodoglycals in aqueous media as a key step proceeds with complete regioselectivity at C-2 and enables access to 2-aryl-glycals with different configurations in excellent yields.